Immunostaining of Voltage-Gated Ion Channels in Cell Lines and Neurons – Key Concepts and Potential Pitfalls - Bocksteins, Elke; Shepherd, Andrew J.; Mohapatra, Durga P.; Snyders, Dirk J. (IntechOpen, 2012)
None